Thin film field-effect transistor with ZnO:Li ferroelectric channel - Armen Poghosyan; Ruben Hovsepyan; Hrachya Mnatsakanyan (Journal of Advanced Dielectrics)
An n-type channel transparent thin film field-effect transistor (FET) using a top-gate configuration on a sapphire substrate is presented. ZnO:Li film was used as a channel, and MgF2 film as a gate insulator. Measurements showed that ZnO:Li films are ferroelectrics with spontaneous polarization [Formula: see text]–5[Formula: see text][Formula: see text]C/cm2 and coercive field [Formula: see text]–10[Formula: see text]kV/cm. The dependences of drain–source current on drain–source voltage at various gate–source voltages in two antiparallel [Formula: see text] states were measured and the values of field-effect mobility and threshold voltage were determined for two [Formula: see text] states are as follows: (a) [Formula: see text][Formula: see text]cm2/Vs, [Formula: see text][Formula: see text]V; (b) [Formula: see text][Formula: see text]cm2/Vs, [Formula: see text][Formula: see text]V. Thus, [Formula: see text] switching leads to a change in FET channel parameters. Results can be used to create a bistable or, more precisely, digital FET.